Guardians of the Galaxy by Abnett & Lanning Omnibus - Abnett, Dan 1965-; Lanning, Andy 1963-; Pelletier, Paul 1970- (Marvel Worldwide, 2016)
All that stands in the way of universal disaster is an unlikely band of cosmic misfits: the Guardians of the Galaxy, retooled for the 21st Century Star-Lord, Gamora, Drax the Destroyer, Rocket Raccoon, Groot, Adam Warlock, Mantis and the all-new Quasar - together with Cosmo the telepathic space dog - take on the universe's most dangerous menaces
Contains material originally published in magazine form as Guardians of the Galaxy #1-25, Thanos Imperative: Ignition #1, #1-6. Devastation #1; Annihilators #1-4; and Annihilators: Earthfall #1-4
Keywords: Comic